1996
DOI: 10.1016/0008-6363(96)00082-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the terminal complement-complex on reperfusion injury, no-reflow and arrhythmias: a comparison between C6-competent and C6-deficient rabbits

Abstract: These results suggest that the lytic C5b-9 complement complex leads to reperfusion injury in the early phase (30 min) of ischaemia, resulting in a larger infarct. After 2 h of ischaemia, complement activation enhances the no-reflow phenomenon but does not affect infarct size. Finally, the C6 status seems to influence the susceptibility to ventricular arrhythmias after coronary artery occlusion, independent of reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 0 publications
1
24
0
4
Order By: Relevance
“…However, C1s-INH-248 treatment retarded C 5b-9 deposition and tissue injury. In a similar approach of myocardial ischemia and reperfusion in C6-deficient rabbits, reduction of myocardial necrosis was related to a reduction in C 5b-9 deposition (29).…”
Section: Discussionmentioning
confidence: 96%
“…However, C1s-INH-248 treatment retarded C 5b-9 deposition and tissue injury. In a similar approach of myocardial ischemia and reperfusion in C6-deficient rabbits, reduction of myocardial necrosis was related to a reduction in C 5b-9 deposition (29).…”
Section: Discussionmentioning
confidence: 96%
“…Each of these activities serves to block the subsequent activation of new C3 molecules (fH acts by promoting decay acceleration of the alternative pathway C3 convertase and as a cofactor for factor I-mediated proteolysis of C3b). Subsequent studies using C6-deficient animals or animals treated with anti-C5 Ab or C5a receptor antagonist indicate an important role for the terminal complement activation products C5a and/or the MAC in warm myocardial IRI (30)(31)(32)(33). More recently, it has been shown that myocardial IRI in a nontransplant setting is dependent on IgM and the lectin pathway (34), and mice deficient in the classical or alternative pathway are not protected from myocardial IRI (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The particular role of the MAC (C5b-9) comes from evidence that rabbits deficient in the complement protein C6 have a reduced infarct size in cardiac ischemiareperfusion models compared with C6-sufficient rabbits. 25 It has traditionally been assumed that liver is the source of complement proteins that participate in these events. But we have recently shown that complement proteins are produced in several organs of the body, including brain and heart.…”
mentioning
confidence: 99%